2020
DOI: 10.1017/s0033291720003165
|View full text |Cite
|
Sign up to set email alerts
|

Influence of COVID-19 on general stress and posttraumatic stress symptoms among hospitalized high-risk patients

Abstract: Influence of COVID-19 on general stress and posttraumatic stress symptoms among hospitalized high-risk patients. Psychological Medicine 1-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…To date, one study reported PTSD symptoms in 12.2% of 41 COVID-19-positive inpatients during hospitalisation. 14 Two studies reported significant post-traumatic stress symptoms in 42.1% 15 and 96.2% 16 of hospitalised COVID-19 patients. However, an early assessment of post-traumatic stress symptoms during hospitalisation may reflect temporary acute stress disorder rather than PTSD.…”
Section: Introductionmentioning
confidence: 98%
“…To date, one study reported PTSD symptoms in 12.2% of 41 COVID-19-positive inpatients during hospitalisation. 14 Two studies reported significant post-traumatic stress symptoms in 42.1% 15 and 96.2% 16 of hospitalised COVID-19 patients. However, an early assessment of post-traumatic stress symptoms during hospitalisation may reflect temporary acute stress disorder rather than PTSD.…”
Section: Introductionmentioning
confidence: 98%
“…11 In high-risk hospital patients with COVID-19 and severe pulmonary, cardiovascular, or oncological diseases, the prevalence rate for post-traumatic stress disorder (PTSD) was 38%. 12 In North Rhine-Westphalia in Germany, the cumulative incidence of COVID-19 up to June 4 was 215 per 100,000 population with a mortality rate of 4.2%. Therefore, COVID-19 was a serious threat at that time.…”
Section: Introductionmentioning
confidence: 99%
“…They found that 12.4% of patients had clinically meaningful PTS. By contrast, a far higher prevalence was reported by Bo et al (2020) in this journal, who used the civilian version of a PTSD questionnaire based on DSM-IV (PCL-C). These authors found a prevalence of PTS of 96.2% in 714 patients with mildhttps://doi.org/10.1017/S003329172000481X Downloaded from https://www.cambridge.org/core.…”
Section: To the Editormentioning
confidence: 71%
“…Other studies report high frequencies of PTS, but do not clearly describe COVID-19 severity. Wesemann et al ( 2020 ) used the PCL-5 and found significant PTS in 8/19 (42%) COVID-19 patients shortly after their presentation to hospital, whereas Chang and Park ( 2020 ) used the PCL-5 to identify PTS in 13/64 (20%) patients assessed 10 weeks after discharge. Either study neither described COVID-19 severity nor indicated the requirement for critical care.…”
mentioning
confidence: 99%